Methyl Gallate Improves Hyperuricemia Nephropathy Mice Through Inhibiting NLRP3 Pathway - Liu, Peng; Wang, Wen; Li, Qiang; Hu, Xin; Xu, Bingyong; Wu, Chen; Bai, Lijie; Ping, Li; Lan, Zhou; Chen, Lvyi (Frontiers in Pharmacology, 2021)
Hyperuricemia nephropathy (HN) is a form of chronic tubulointerstitial inflammation, caused by the deposition of monosodium urate crystals (MSU) in the distal collecting duct and medullary interstitium, associated with a secondary inflammatory reaction. Numerous published reports indicated that NLRP3 inflammasome pathway play crucial roles in HN symptoms. The present study aims to investigate the protective effects of methyl gallate on HN mice and the underlying mechanisms. An HN model was established by intraperitoneal injection of potassium oxide (PO) to assess the effect of methyl gallate on renal histopathological changes, renal function, cytokine levels and expressions of NLRP3-related protein in HN mice. Moreover, in vitro models of lipopolysaccharide (LPS)-stimulated bone marrow-derived macrophages (BMDMs) and human peripheral blood mononuclear cells (PBMCs) were established to explore the mechanism of methyl gallate on NLRP3 inflammasome activation. The results showed that methyl gallate significantly ameliorated HN by inhibiting uric acid production and promoting uric acid excretion as well as ameliorating renal injury induced by NLRP3 activation. Mechanistically, methyl gallate is a direct NLRP3 inhibitor that inhibits NLRP3 inflammasome activation but has no effect on the activation of AIM2 or NLRC4 inflammasomes in macrophages. Furthermore, methyl gallate inhibited the assembly of NLRP3 inflammasomes by blocking the ROS over-generation and oligomerization of NLRP3. Methyl gallate was also active ex vivo against ATP-treated PBMCs and synovial fluid mononuclear cells from patients with gout. In conclusion, methyl gallate has a nephroprotective effect against PO-induced HN through blocking the oligomerization of NLRP3 and then exerting anti-inflammatory activity in the NLRP3-driven diseases.